Potency of Salicylic Acid to Disrupt the Growth and Development of Papaya Mealybug, Paracoccus marginatus (Hemiptera: Pseudococcidae) - Liza Octriana; Nugroho Susetya Putra; Suputa Suputa (Jurnal Perlindungan Tanaman Indonesia, 2019)
Mealybug is an important pest of papaya plants. Induction of plant resistance using elicitors, such as salicylic acid, might have the potency to reduce the extent of crop damage by mealybug. Therefore, a laboratory experiment was performed to determine the effect of salicylic acid on feeding preference, fecundity, oviposition period, and longevity of papaya mealybug adult, Paracoccus marginatus. The results showed that the application of salicylic acid increased total phenol content on papaya leaf (r = 0.57) hence decreased in feeding preferences and fecundity, slowed down the growth period of the nymph and pre-oviposition period, and prolonged the longevity of mealybug. The potency of using salicylic acid to control of mealybug on papaya in integrated pest management was discussed in this paper.